Expectations and Preferences of Iranian Infertile Couples from Healthcare System after Unsuccessful Treatment with Assisted Reproductive Technologies - samira Ebrahimzadeh-Zagami; Roksana Janghorban; Robab Latifnejad-Roudsari (Mashhad University of Medical Sciences, 2020)
Background & aim: Increased number of unsuccessful cycles of infertility treatments might result in an increase in couples' physical and psychological problems, which affect their expectations from family, society and healthcare system. The present study aimed to explore the expectations and preferences of Iranian infertile couples from healthcare system after unsuccessful treatment with assisted reproductive technologies. Methods: This descriptive qualitative study was carried out during 2016-2017 in one of the referral infertility clinics in Mashhad, Iran. Data collection was completed through face-to-face semi-structured interviews with 29 infertile couples selected by purposive sampling. The collected data were analyzed in four stages according to the Graneheim and Lundman method using MAXQDA software (version 2010). Results: The overarching theme of "expecting improvement of treatment process" included three categories of expecting enhancement of therapeutic and healthcare services, demanding financial services, and requesting for more male involvement in the treatment process were emerged. Infertile couples expected continuous high-quality follow-up appointments and requested for a systematic recording of infertility-related data. They also expected that healthcare system provide them the basis for a wide range of governmental facilities including medical loans with low interests and insurance facilities. Additionally, they preferred that physicians to communicate with both partners during consultation and expected healthcare system to provide counselling centres for male partners. Conclusion: Understanding infertile couples' expectations and preferences from healthcare system after unsuccessful infertility treatment could help policy makers to adopt appropriate policies and programs to meet these vulnerable population needs, so that improve their treatment outcomes.